PP.31.04: ACCURACY OF HOME BLOOD PRESSURE MONITORING IN HYPERTENSION MANAGEMENT. (June 2015) - Di Monaco, S.; Rabbia, F.; Covella, M.; Frualdo, M.; Fulcheri, C.; Totaro, S.; Testa, E.; Berra, E.; Pappaccogli, M.; Perlo, E.; Veglio, F.
Abstract : Objective: Current guidelines suggest Home Blood Pressure Monitoring (HBPM) as a complementary measurement method compared with Ambulatory Blood Pressure Monitoring (ABPM), in identification of arterial hypertension (AH). The main purpose of our study was to identify which factors increase HBPM accuracy, testing a short HBPM schedule compared with ABPM. We tried to identify the best HBPM device and which patients were more reliable in HBPM execution. Design and method: We enrolled 321 consecutive patients who performed ABPM in our Hypertension Centre and completed a short HBPM schedule (two measurements, twice daily, for four days) between November 2011 and December 2014. First we compared three techniques: arm and wrist automated devices and manual sphygmomanometers. For the better accuracy we continued our analyses on 270 people who used automated arm devices. Results: Pearson correlation coefficients of arm and wrist automated devices and manual sphygmomanometers for systolic blood pressure (SBP) were 0.59, 0.20 and 0.62, and for diastolic blood pressure (DBP) were 0.72, 0.33 and 0.59. ROC curves for automated arm devices described AUC for SBP of 0.795 and for DBP of 0.847. Box plots of daily mean pressure values did not show significant differences. No significant difference was found between first day coefficient and the others for SBP, p-value 0.06, and for DBP, p-value 0.262. Men and women correlation coefficient were respectively 0.65 and 0.51 for SBP and 0.75 and 0.67 for DBP. Dividing patients by age, the correlation coefficient for SBP were 0.52 (<= 40 years), 0.55 (40–65), 0.69 (>= 65) and for DBP were respectively 0.74, 0.62, 0.66. Conclusions: HBPM has a moderate correlation and a good accuracy in the identification of AH compared with ABPM. We confirm the need to use automated arm devices in HBPM execution. In contrast with current guidelines we do not suggest the elimination of first day measurements. Men and over 65 years patients have more reliability in HBPM execution.